BIOCHEMICAL PROFILE OF DEONI COWS SUPPLEMENTED WITH HAEMATINIC AND IRON FOR INDUCTION OF ESTRUS - MARKANDEYA, N M; PATIL, A D; BHARKAD, G P (The Indian Journal of Animal Reproduction, 2023)
Postpartum anestrus Deoni cows were treated with haematinic and mineral supplements and itwas observed that 83.33 per cent cows responded to Cofecu plus treatment with 41.67 per centconceptions, 91 .67 per cent cows responded to Cofecu + ovifertin treatment with 75.00 per centconceptions and 91 .67 per cent cows responded to Ferrocom + Ovifertin treatment with 66.67 per centconceptions. The post treatment levels of haemoglobin (g% ), serum protein (go/o ), serum copper (mcg% ),serum cobalt (mcg%) and serum iron (mcg%) were found to13.45 ± 00.04, 13.46 ± 00.04, 13.45 ± 00 .04; 07.75 ± 00.21, 08.99 ± 00.21, 09.06 ± 00.21; 102.28 ± 07.19, 106.26 ± 07.1, 102.52 ± 07.19; 02.48 ± 0.005, 02.54 ± 0.005, 02.20 ± 0.005 and 200.47 ± 20.10, 202.22 ± 20.10, 196.20 ± 20.10 respectively. Blood biochemical analysis proved significant increase in the levels of haemoglobin, Iron, copper and cobalt with the herbal therapies in all treatment groups than that of the control groups withexception of protein levels.
Keywords: Biochemical; Deoni; Estrus; Haematinic; Minerals